The Effects of the Glyphosate-based Herbicide WeatherMax on Sexual Differentiation and Growth in the Wood Frog (Lithobates sylvaticus) - Robertson, Courtney (Université d'Ottawa / University of Ottawa, 2013)
Glyphosate-based herbicides are the dominant pesticide on the market and are utilized worldwide in both the agricultural and forestry industries. Their prevalence comes at a time when concern over the potential effects of pesticide application in amphibian spawning grounds is growing. The primary goal of this thesis was to determine if the glyphosate-based herbicide WeatherMax® has the potential to disrupt sexual differentiation and growth in the wood frog (Lithobates sylvaticus) in a pulse exposure at the predicted maximal environmental concentration (PMEC) of 2.88 mg acid equivalent per liter. This was carried out in laboratory, mesocosm and in-situ field exposures, in an attempt to determine how a potential disruption might vary between experimental environments. In this study, tadpoles from three split-wetlands targeted at the PMEC for WeatherMax were found to display no significant change in survival or growth, however gene expression of several genes involved in steroidogenesis during sexual differentiation (cyp19, cyp17, star, foxl2) were found to be affected. The effects on these genes appeared to be dependant on the exposure concentration of WeatherMax in each wetland, which varied even though all three wetlands were meant to target the PMEC. The wetland that was measured as having the highest herbicide concentration (PMEC 13) was found to have a female biased sex ratio. The results found in the field varied from those found in the more artificial exposures. In the laboratory the PMEC of WeatherMax experienced complete mortality, whereas in the mesocosms survival was not significantly affected. Sex ratios were unaffected in the laboratory, however at the PMEC there was a significant male bias in the mesocosms. The discrepancies in the results obtained from the different exposure types highlights the importance of real world exposures. That the same concentration that caused complete mortality in the laboratory caused sublethal effects in the field is of importance as it denotes that these endpoints may not be easily investigated in these synthetic exposures. This project is a part of the Long Term Experimental Wetlands Area (LEWA) and contributes to the body of information amassed therein on the impact of a glyphosate-based herbicide on amphibians in a wetland ecosystem.
Keywords: Herbicide; Amphibian; Glyphosate; Polyethoxylated tallowamine; Gene Expression (star, cyp19, cyp17, foxl2); Wetland